2016
DOI: 10.1080/10934529.2016.1170431
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of PAHs and other gaseous pollutants in the atmosphere of a rural area

Abstract: In this study, concentrations of polycyclic aromatic hydrocarbons (PAHs) bound to PM10 particles were measured in a Croatian rural area. Considering that by now only a limited number of studies have provided data on pollutant concentrations for rural areas, our aim was to do so by determining the PAH levels, their mutagenic effect and relationship with meteorological conditions and other gaseous pollutants (NO, NO2, NH3). In this investigation, samples of PM10 particles were collected on quartz filters for 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Previous studies of air quality in continental Croatia have shown that ambient air is polluted with PM and PAHs, especially during the colder part of the year (heating season) [ 84 , 85 , 86 , 87 , 88 ]. Levels of ambient air pollutants measured in Zagreb during this study did not differ significantly from values obtained in earlier investigations [ 85 , 87 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of air quality in continental Croatia have shown that ambient air is polluted with PM and PAHs, especially during the colder part of the year (heating season) [ 84 , 85 , 86 , 87 , 88 ]. Levels of ambient air pollutants measured in Zagreb during this study did not differ significantly from values obtained in earlier investigations [ 85 , 87 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…BaP contamination poses a serious health hazard to humans and those affected by diseases [ 25 , 65 , 66 , 67 , 68 ]. It is well documented that exposure to BaP and other chemicals found in soot, cigarette smoke, and exhaust fumes is associated with cancer in humans [ 5 , 6 , 7 , 8 , 9 , 58 , 69 , 70 ]. Due to its lipophilic nature, BaP can easily cross the cell membrane and accumulate in cells where it complexes with the aryl hydrocarbon receptor (AhR), stimulating its metabolism through induction of cytochrome P450 isoforms 1A1 (CYP1A1) and 1B1 (CYP1B1) [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure can result in very high levels of BaP accumulating in the human body. Limited studies have provided data on pollutants in rural areas [ 6 ]. In the rural areas the source of BaP would be burning wood for example.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations